2017
DOI: 10.1210/en.2016-1640
|View full text |Cite
|
Sign up to set email alerts
|

High-Sugar, but Not High-Fat, Food Activates Supraoptic Nucleus Neurons in the Male Rat

Abstract: Oxytocin is a potent anorexigen and is believed to have a role in satiety signaling. We developed rat models to study the activity of oxytocin neurons in response to voluntary consumption or oral gavage of foods using c-Fos immunohistochemistry and in vivo electrophysiology. Using c-Fos expression as an indirect marker of neural activation, we showed that the percentage of magnocellular oxytocin neurons expressing c-Fos increased with voluntary consumption of sweetened condensed milk (SCM). To model the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 59 publications
4
31
0
5
Order By: Relevance
“…Interestingly, however, they are inhibited by gavage of isocaloric cream 119. 111,114,115 The effects of CCK 116 and probably those of secretin too are mediated by activation of gastric vagal afferents that lead to activation of neurones in the nucleus tractus solitarii (NTS), 117 including the noradrenergic A2 cells that project directly to oxytocin cells.…”
mentioning
confidence: 99%
“…Interestingly, however, they are inhibited by gavage of isocaloric cream 119. 111,114,115 The effects of CCK 116 and probably those of secretin too are mediated by activation of gastric vagal afferents that lead to activation of neurones in the nucleus tractus solitarii (NTS), 117 including the noradrenergic A2 cells that project directly to oxytocin cells.…”
mentioning
confidence: 99%
“…The hypothalamic neurohormone oxytocin has an emerging role in appetite control, and may be involved specifically in an anorexigenic response to carbohydrate intake . Oxytocin may have a neuromodulatory role in the SuM, and we have previously shown that gavage of a high‐sugar food increases the electrical activity of oxytocin neurones in the rat supraoptic nucleus, which may lead to somatodendritic oxytocin release to target the SuM. Alternatively or additionally, ghrelin signalling may be relevant.…”
Section: Discussionmentioning
confidence: 97%
“…Brains were processed for Fos and TH‐like immunoreactivity, imaged and quantified as described previously . To detect Fos‐like immunoreactivity, we used anti‐Fos rabbit primary antibody (dilution 1:100 000; 226 003; Synaptic Systems, Göttingen, Germany) and a biotinylated horse anti‐rabbit immunoglobulin (Ig)G secondary antibody (dilution 1:500; BA‐1100; Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin plays an important role in the termination of food intake, and oxytocin neurons are activated following food consumption or ingestion [41,42]. Hypothalamic oxytocin mRNA expression is reduced with fasting and recovers with refeeding [43] or the administration of leptin [44].…”
Section: Physiological Role Of Oxytocin In Feeding Regulationmentioning
confidence: 99%